2017
DOI: 10.1016/j.ijcard.2016.11.105
|View full text |Cite
|
Sign up to set email alerts
|

Early initiation of eicosapentaenoic acid and statin treatment is associated with better clinical outcomes than statin alone in patients with acute coronary syndromes: 1-year outcomes of a randomized controlled study

Abstract: UMIN Clinical Trials Registry (UMIN-CTR); Registry Number, UMIN000016723; URL, http://www.umin.ac.jp/ctr/index-j.htm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 38 publications
(42 reference statements)
3
47
0
1
Order By: Relevance
“…Furthermore, TG reduction lowers several inflammatory markers associated with CV risk, and subgroup and post hoc analyses of outcome studies suggest possible reductions in major CV events with TG‐lowering therapy 3, 4, 5, 6, 7, 8, 9, 10, 11. Finally, studies administering higher‐dose EPA suggest additional beneficial effects beyond lipid‐lowering that may be unique to EPA relative to other TG‐lowering therapies, such as beneficial changes in coronary plaque characteristics, which may lead to reductions in major CV events 4, 16, 25, 26, 27, 28, 29, 30, 31, 32, 33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, TG reduction lowers several inflammatory markers associated with CV risk, and subgroup and post hoc analyses of outcome studies suggest possible reductions in major CV events with TG‐lowering therapy 3, 4, 5, 6, 7, 8, 9, 10, 11. Finally, studies administering higher‐dose EPA suggest additional beneficial effects beyond lipid‐lowering that may be unique to EPA relative to other TG‐lowering therapies, such as beneficial changes in coronary plaque characteristics, which may lead to reductions in major CV events 4, 16, 25, 26, 27, 28, 29, 30, 31, 32, 33…”
Section: Discussionmentioning
confidence: 99%
“…In addition to beneficial changes to TG‐rich lipoproteins and other plasma lipid markers, some clinical studies with higher‐dose EPA also suggest beneficial effects on markers of oxidation and inflammation, coronary plaque characteristics, and major CV events 16, 25, 26, 29, 31, 32, 33. For example, in contrast to the fenofibrate and niacin studies, JELIS found a 19% relative risk reduction in CV events in statin‐treated patients with relatively normal TG but a more pronounced 53% reduction in the subgroup with mixed dyslipidemia, specifically TG ≥150 mg/dL and HDL‐C <40 mg/dL 4, 16.…”
Section: Introductionmentioning
confidence: 99%
“…The relative reduction in major coronary events was comparable across a range of LDL-C levels, suggesting that reduction in serum LDL-C levels was not a key factor in the observed CV risk reduction [48]. Additional support for the potential role of EPA in CV risk reduction comes from a prospective, single-center, randomized, open-label trial of 241 Japanese patients with acute coronary syndrome undergoing primary percutaneous coronary intervention (PCI) [49]. Patients were randomized to EPA 1.8 g/day (purified ethyl ester) plus a statin (pitavastatin 2 mg/day) or statin alone [49].…”
Section: Imaging Methods Key Findings Angiographymentioning
confidence: 99%
“…Additional support for the potential role of EPA in CV risk reduction comes from a prospective, single-center, randomized, open-label trial of 241 Japanese patients with acute coronary syndrome undergoing primary percutaneous coronary intervention (PCI) [49]. Patients were randomized to EPA 1.8 g/day (purified ethyl ester) plus a statin (pitavastatin 2 mg/day) or statin alone [49]. Early initiation of EPA/statin within 24 h after successful PCI resulted in a significantly lower risk of CV events compared with statin alone (relative risk of CV events at 1 year, 9.2% for EPA/statin, and 20.2% for statin alone; absolute risk reduction 11%; P = 0.02) [49].…”
Section: Imaging Methods Key Findings Angiographymentioning
confidence: 99%
See 1 more Smart Citation